The Mysticism of Cultural Education in Indonesia: Phenomenological Review of Nyabis in Madura - Achmad Maulidi; Moh. Wardi; Musleh Musleh (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2023)
Almost all Madurese practice Nyabis culture with various statuses and social stratifications ranging from the lower to the upper classes; interestingly, their arrival is massive in a certain period and routine every month, twice a month, every week and even twice a day. This paper aimed to describe the Nyabis culture holistically. This paper used a phenomenologically qualitative method, with data collection methods of semi-structured interviews, non-participant observation, and documentation. Data analysis uses the interactive model of Miles Huberman and Saldana. The results found that the culture of Nyabis continues to be maintained and carried out from the historical side of the famous sacred figures, pious and other advantages that occur from generation to generation; the next side is due to unusual, illogical, and mystical intermediaries. The irrational, mystical phenomenon and social reality of Nyabis cultural actors have succeeded in creating fanaticism within the community. This fanaticism stems from knowledge gained from social interactions in the form of conversations or stories that arouse curiosity and are then reinforced by concrete evidence of the perpetrators of this culture so that the Kiai continues and is increasingly believed to have advantages to solve various problems and needs of the community.